Numerical evaluation of contemporary excavator bucket designs using finite element analysis - Mughal, Khurram Hameed; Bugvi, Salman Abubakar; Qureshi, Muhammad Asif Mahmood; Khan, Muhammad Aamir; Hayat, Khazar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bucket is key and primary component of heavy construction machinery such as excavators. It has to bear high impact loads during digging process, resulting in large stress and deformations. This research work has been focused on reducing stress and deformations produced in excavator bucket due to digging. For this purpose, different design patents of excavator buckets (including ornamental designs) were considered. Various models of excavator buckets were developed by varying geometrical parameters such as number of blade teeth/tips and bucket curvature. Finite element analysis of these models was carried out by using ANSYS in order to determine stress and strains. Maximum values of Von Mises stress, principal stress, factor of safety and total deformation were evaluated numerically for all three-dimensional geometric models. Excavator bucket with least values of stress and deformations, but largest factor of safety, was identified through numerical computations. Mechanical performance of ornamental buckets having quarter circular curvature with 6 blade teeth was observed to be better as compared to designs having single blade strip or 5 blade teeth. Mass reduction up to 2.5%, while the stress reduction and factor of safety enhancement up to 9.6% was achieved by incorporating 6 blade teeth in ornamental design of excavator bucket.